2012
DOI: 10.1016/j.jclepro.2011.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Procedures and criteria to develop and evaluate household sustainable consumption indicators

Abstract: Communication about very complex problems like household sustainable consumption in simple terms is still a major challenge. Despite the diversity of tools to measure household consumption, clearer indicators are needed to more effectively communicate with the general public. The main objective of this research was to develop an approach to define the main procedures and criteria to built household sustainable consumption assessment tools based on indicator sets. A review of available household sustainable con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(52 citation statements)
references
References 66 publications
0
46
0
6
Order By: Relevance
“…Consumers make choices about the products and services they use and their lifestyles determine their consumption patterns (Caeiro et al, 2012, p73, Halme et al, 2004. Baiocchi et al (2010, p67) found that in the UK 75% of GHG emissions were associated with lifestyle choices, and the household and transport sectors accounted for the largest shares.…”
Section: The Role Of Behaviours In Energy Managementmentioning
confidence: 99%
“…Consumers make choices about the products and services they use and their lifestyles determine their consumption patterns (Caeiro et al, 2012, p73, Halme et al, 2004. Baiocchi et al (2010, p67) found that in the UK 75% of GHG emissions were associated with lifestyle choices, and the household and transport sectors accounted for the largest shares.…”
Section: The Role Of Behaviours In Energy Managementmentioning
confidence: 99%
“…Generally the categories of transportation, housing and food make the largest contributions (Jones and Kammen 2011 ;Caeiro et al 2012 ;Tukker 2006 ;Tukker and Jansen 2006 ). For example, Benders et al ( 2012 ) found that these three domains account for nearly three quarters of carbon emissions and inclusion of the next largest category, recreation, accounted for around 85 % of average carbon footprints in The Netherlands.…”
Section: Composition Of Household Carbon Footprintsmentioning
confidence: 99%
“…Household type A number of studies (Lenzen et al, 2004;Ferrer-i-Carbonell and Van Den Bergh, 2004;Barr and Gilg, 2006;Jensen, 2008;Kerkhof et al, 2009;Caeiro et al, 2012) have discussed the connection between socio-economic characteristics of households and their consumption patterns. Additionally, Luck et al (2009) found that immigrants are generally less familiar with the local environment and land management practices than native residents.…”
Section: Environmental Awareness Demographic Characteristicsmentioning
confidence: 99%